Genome-Wide Identification and Expression Analysis of the NHX (Sodium/Hydrogen Antiporter) Gene Family in Cotton - Fu, Xiaokang; Lu, Zhengying; Wei, Hengling; Zhang, Jingjing; Yang, Xu; Wu, Aimin; Ma, Liang; Kang, Meng; Lu, Jianhua; Wang, Hantao; Yu, Shuxun (Frontiers in Genetics, 2020)
The sodium/hydrogen antiporter (NHX) gene family with the Na+/H+ exchange protein domain is a transporter of sodium and hydrogen ions and plays an important role in the response of plants to salt stress. Studying the response of cotton to salt stress through the comprehensive identification and analysis of NHX genes in several species and of their roles in salt tolerance mechanisms is of great significance. In this study, 23, 24, 12 and 12 NHX genes were identified from Gossypium. hirsutum, G. barbadense, G. arboreum and G. raimondii, respectively. Phylogenetic analysis showed that these genes were mainly divided into three clades with significant subcellular localization, namely, endosome (Endo-class), plasma membrane (PM-class) and vacuole (Vac-class). By analysing the structure of NHX genes and proteins, it was found that each branch of the NHX gene family was structurally conserved, and collinear analysis showed that NHX genes were mainly expressed through whole genome and segmental duplication. The Ka/Ks values showed that the NHX gene family experienced strong purifying selection during long-term evolution. Cis-acting element analysis showed that the NHX gene family may be related to the regulation of ABA and MeJA hormones. Additionally, transcriptomic data analysis and qRT-PCR showed that GhNHXs exhibited different expression patterns in each tissue and under different salinities. These results provide an important reference for us to further understand and analyse the molecular regulation mechanism of cotton NHX genes.